Compact Objects in Alternative Gravities - Jose Luis Blázquez-Salcedo; Burkhard Kleihaus; Jutta Kunz (Universe, 2022)
We address neutron stars and black holes in alternative gravities, after recalling their basic properties in General Relativity. Among the plethora of interesting alternative gravities we here focus on an interesting set of scalar-tensor theories. We discuss the phenomenon of spontaneous scalarization, that is, matter induced for neutron stars and curvature induced for black holes. Along with other relevant physical properties, we address the quasi-normal modes of these compact objects. In particular, we consider universal relations of neutron stars to largely reduce the dependence on the equation of state, and we briefly address the shadow of black holes.